A Combined Approach for Treatment of Developmental Groove Associated Periodontal Defect. A Case Report - Andreana, Sebastiano (Journal of periodontology (1970), 1998)
Developmental grooves are not rare and often appear on maxillary lateral incisors. This may represent a challenge and sometimes tooth extraction is inevitable. This case report describes a combined technique of regenerative and antimicrobial/root conditioning used to treat a maxillary lateral incisor in a 32‐year‐old woman. Tooth #10 presented a periodontal probing depth, of 8 mm below the cingulum, associated with a developmental groove. The tooth was vital. After initial preparation, a palatal miniflap was raised, granulation tissue was eliminated by means of ultrasonic bactericidal curettage and radicoloplasty performed. The surface was then treated for 3 minutes with tetracycline‐HCl solution (100mg/ml), and the defect filled with sterile, medical grade, calcium sulfate. Clinical measurements were retaken at 6, 12, and 18 months. The results indicated a reduction of probing depth to 2 mm, reestablishment of the lamina dura, and radiographical evidence of bone growth. This combined treatment allowed the tooth to be saved, the palatal surgical approach did not alter the esthetics of the area, and its simplicity is recommended. J Periodontol 1998;69:601–607.